The scales of literary study - Kalantzopoulou, Maro (Primerjalna književnost, 2013)
This article discusses the ways in which literary scholarship has conceptualized the relations between different literary cultures. It suggests an application of a multiple-scale analysis of literary phenomena, and explores the characteristics of certain national, transnational, connected, comparative, and world literatures.
Keywords: comparative literature; primerjalna književnost; svetovna književnost; nacionalne književnosti; svetovni sistem; kulturna identiteta; nadnacionalnost